Opioides para o tratamento da síndrome das pernas inquietas - Oliveira, Cesar Osorio De [UNIFESP] (2019)
Introduction: Restless leg syndrome, also known as Willis-Ekbon disease, is a neurological disorder characterized by the urgency to move the affected body segment, most often the legs, because of unpleasant and uncomfortable sensations that predominate during rest sitting or lying down) and at dusk or early evening. Typically, movement results in relief of discomfort, at least during its execution. It can be classified into primary and secondary forms. Regarding pharmacological treatment, dopaminergic, antiepileptic, benzodiazepine and opioid agonists are currently used. Objective: To evaluate the efficacy and safety of the treatment of the restless legs syndrome in its primary form with opioids. Method: systematic review with electronic search of randomized and / or quasi-randomized clinical trials; the Cochrane CENTRAL and Cochrane Library, MEDLINE, EMBASE and LILACS databases were accessed. Indexed descriptors were used in Medical Subject Headings, Emtree Thesaurus and Descriptors in Health Sciences. We also searched for reviews, texts, books and unpublished articles, among others. Results: 2935 records were found, 2933 of which were by electronic means and 2 by manual search, of which 45 were excluded by duplication, 2886 after analysis of titles and abstracts, remaining 4 studies that were evaluated in their full text. Of these 4, three were excluded because they did not meet the inclusion criteria, one study included in the present systematic review. This study deals with the evaluation of the use of opioids (slow release oxycodone / naloxone formulation) in progressive doses, compared with placebo. Discussion : study was well structures but there was high dropout rate, setting highfriction bias. In the group that received drugs, eighty-four percent of the individuals developed adverse events, mainly headache, fatigue, somnolence and symptoms related to gastrointestinal system; 9.8 % dropped out because of adverse events. Conclusion : there is evidence of moderate quality to support the use of opioids for the treatment of RLS in patients resistant to the firs-choice treatment. The prescription of theses drugs should be based on clinical esperience and with precautions related to the potential for abuse, dependence and adverse events. No patient in opioids complained that their symptoms worsened over the study period.